Molecular and functional indication of Chalcone synthase in Boesenbergia rotunda / Fatemeh Shahhosseini - Shahhosseini, Fatemeh (2014)
Chalcone synthase (CHS) is a key enzyme in flavonoids biosynthesis pathway, which catalyzes the condensation of three acetate residues from malonyl-CoA with pcoumaroyl- CoA to form naringenin chalcone. This step is the first committed step of the phenylpropanoid pathway, which regulates other sub-branches to produce flavonoids, isoflavonoids, anthocyanin, chalcone, and other flavonoids compounds in plants. Several studies have shown that the flavonoids and chalcones are pharmaceutically active in Boesenbergia rotunda, but the purification is often impossible due to the low concentration of these flavonoids. Most studies recently focused on the individual genes of the pathway such as CHS gene to overproduce certain compounds like panduratin A. Comparison of CHS gene sequence from different species revealed that CHS gene is structurally conserved. In this study, a core fragment of CHS gene was amplified using nested PCR. The amplicon of 584bp length encoding ~194 amino acids was confirmed as part of the second exon of CHS gene, however the complete triad active site was not present in the core fragment of B. rotunda CHS protein. The core fragment showed that the nucleotide and amino acid sequence of the second exon of CHS gene is variable. Gene expression analysis indicated the presence of CHS transcript in leaves, rhizomes, roots, and shoot base of B. rotunda with the highest expression level in shoot base. The full-length B. rotunda CHS gene was then amplified and cloned from B. rotunda rhizome using rapid amplification of cDNA ends. The amplicon of 1,257bp length containing a coding sequence of 1,176bp, which codes for 391 amino acids with the molecular mass of 43.22kDa and a predicted isoelectric point of 6.79 was obtained. Comparative and bioinformatic analyses revealed that the deduced protein of all nine variants (HQ176338-HQ176346) of B. rotunda CHS protein were highly homologous to CHSs from other plant species. Phylogenetic analysis indicated that the B. rotunda CHS protein was in a subgroup with Dendrobium CHS. The prediction of the secondary structure of all nine variants of B. rotunda CHS protein mainly showed α-helix and extended strand. The prediction of three-dimensional structure of nine variants of B. rotunda CHS protein showed the highest similarity to alfalfa CHS (1CGZ) having CHSspecific conserve motifs and the CHS-family signature sequence GFGPG. The docking analysis showed that panduratin A could not be the direct product of B. rotunda CHS protein.